1993
DOI: 10.1159/000139061
|View full text |Cite
|
Sign up to set email alerts
|

Are m-Cholinoceptors of Guinea Pig Gallbladder Smooth Muscle of m<sub>4</sub> Subtype?

Abstract: The antagonism of carbachol-induced contractions of guinea pig gallbladder smooth muscle strips via selective antagonists, methoctramine, HHSiD, pf-HHSiD and DABDMA has been investigated in order to find out the m-cholinoceptor subtype(s) of gallbladder smooth muscle. All m-cholinoceptor antagonists examined, displaced the concentration-response curves to the right parallel in a concentration-dependent manner without affecting the maximum response. Schild analysis of data was consistent with competitive antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The gallbladder was a uniquely interesting smooth muscle based on the proposed presence of M 4 receptors and their role in mediating smooth muscle contractility (Ozkutlu et al, 1993;Karaalp et al, 1999;Akici et al, 2000). Carbamylcholine-induced contraction in gallbladder from M 4 receptor knockout mice was dextrally shifted compared with the response in gallbladder from wild-type mice, suggesting that the M 4 receptor participated in the contraction to carbamylcholine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gallbladder was a uniquely interesting smooth muscle based on the proposed presence of M 4 receptors and their role in mediating smooth muscle contractility (Ozkutlu et al, 1993;Karaalp et al, 1999;Akici et al, 2000). Carbamylcholine-induced contraction in gallbladder from M 4 receptor knockout mice was dextrally shifted compared with the response in gallbladder from wild-type mice, suggesting that the M 4 receptor participated in the contraction to carbamylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of a prominent role for M 3 and a more modest role for M 2 receptors in muscarinic-induced contraction of gallbladder is consistent with previous observations documenting a similar role for these receptors in carbamylcholine-induced contraction of other smooth muscles such as mouse trachea, stomach fundus, and urinary bladder (Stengel et al, 2000). In addition to these muscarinic receptors, the M 4 receptor has also been proposed to play an important role in contractility of the guinea pig gallbladder (Ozkutlu et al, 1993;Karaalp et al, 1999;Akici et al, 2000). The possibility that M 4 receptors may be involved in gallbladder contraction deserves careful consideration because it markedly contrasts with the lack of M 4 receptor involvement in the contraction of other smooth muscle preparations (Stengel et al, 2000).…”
mentioning
confidence: 99%
“…Evidence acquired from canine atrial tissue suggests a potential role for AChM4R in the control of K ϩ channels (11,95). AChM4R has been shown to be involved in the contractile responses of smooth muscle in the uterus and gall bladder, suggesting that it may have a role in contractile responses in other smooth muscle tissues, but more evidence is needed (27,85,86). A recent study using muscarinic KO mice suggested that AChM4R receptors may also play a minor role in facilitating AChM2R receptor-mediated bradycardia, but further studies are warranted to elucidate what role, if any, AChM4R plays in the cardiovascular system (98).…”
Section: Muscarinic M4 Receptormentioning
confidence: 99%